PENGARUH KEMANDIRIAN DAERAH, INTERGOVERNMENTAL REVENUE DAN KEKAYAAN DAERAH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH( LKPD ) (Studi pada Laporan Keuangan Pemerintan Daerah Kabupaten/Kota di Propinsi Riau Tahun 2009-2014) - Dhaulika Hidayah; Yusralaini Yusralaini; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the influence ofindependence of The region, intergovernmental revenueand regional wealthonlevel of financial statement disclosures.The population in this study are all local government financial report in Riau Provincefrom 2009 to 2014. The number of samples are processed as many as 53local government financial report listed in Riau Province from 2009-2014. Data analysis technique used is multiple regression analysis were processed with SPSS Windows 19. The results show that independence of the region, intergovernmental revenue, and regional wealth have significant towards financial statement disclosures. Each of them have significant (0.022),(0.007),(0.011) less than (0.05). Overall, it is known that independence of The region, intergovernmental revenueand regional wealth has an effect on the level of financial statement disclosures of 31.6 %. While 68.4% is influenced by other variables not examined in this study.Keywords : Independence, Intergovernmental, Wealth, Disclosures